Green Innovation as a Mediator between CSR, Ownership Concentration, and Financial Performance - Dewi, Vinda Auralia Kesuma; Hadiwibowo, Imam; Azis, Mohammad Taufik (International Research Journal of Business Studies, 2024)
This study examines the mediating role of green innovation in the relationship between Corporate Social Responsibility (CSR), Ownership Concentration (OC), and Financial Performance (FP) in the energy and basic materials sector in Indonesia. Data from 20 companies from 2020 to 2023 were analyzed using panel data regression and Sobel test. The findings show that CSR positively affects GI but has no significant direct effect on FP. Meanwhile, OC has no significant effect on GI and a negative effect on FP. Additionally, GI negatively affects financial performance but mediates the positive relationship between CSR and FP. However, GI does not significantly mediate the relationship between OC and FP. These results highlight the importance of aligning sustainable practices with a company's long-term strategy to enhance company value. This research contributes to understanding the dynamic interaction between CSR, governance structure, and innovation in achieving sustainability and profitability goals.